Grid computing towards a global interconnected infrastructure - Preve, Nikolaos P. (Springer, 2011)
Grid computing provides a mechanism for integrating, coordinating, and sharing heterogeneous computer resources.  This continually evolving field now aims to completely disaggregate current computer platforms and distribute them across a network as resources that can be called into action by any eligible user or machine at any time. This accessible and broad-ranging text/reference presents valuable research and results from many of the major projects involved in the emerging global grid infrastructure.  With a particular focus on the practical advantages and applications of grid computing including real case studies the book provides an in-depth study of grid technology for a wide range of different needs. Topics and features: Presents contributions from an international selection of experts in the field Provides summarizing abstracts and conclusions for each chapter Examines a remote instrumentation infrastructure, and a methodology to support e-science applications on e-infrastructures Describes the GEMS storage system, and pipeline workflows for optimizing end-to-end performance in wide-area networks Investigates semantic grid system architecture, social grid agents, and monitoring platforms designed for large-scale distributed systems Explores job control using service-level agreements Introduces the Composable Services Architecture for dynamic service provisioning, and the semantically driven communication middleware platform, Phoenix Discusses the PhyloGrid application, and a numerical simulation performed using grid computing The deep insights that can be gleaned from the text make it a highly useful tool for researchers and professionals alike.  Graduate students will also benefit from the extensive analysis on currently available grid systems.